THE IMPORTANCE OF TECHNOLOGICAL CREATIVITY IN ENHANCING KNOWLEDGE MANAGEMENT AND COMPETITIVE ADVANTAGE AS A DEFENSIVE DIMENSION IN PRODUCTIVE COMPANIES-AN APPLIED STUDY AT THE GENERAL COMPANY FOR GAS FILLING AND SERVICES - BABYLON BRANCH - Athraa Saad Hassan (Scholar Express Journals, 2025)
A company's ability to withstand competition is closely linked to improved information technology and effective knowledge management. These elements are essential to enhancing an organization's ability to maintain and grow its competitive advantage. This study aims to examine the impact of technological innovation on enhancing knowledge management and an organization's competitive advantage. This study, which used knowledge management as an intervening variable, relied on a field survey methodology, with the participation of department heads and employees at the Sadah Gas Plant in Babil Governorate. The sample size was (100) individuals. Data were collected using a questionnaire and analyzed using SPSS to assess the relationships between variables. The results indicate that technological innovation has a significant positive impact on knowledge management. These findings underscore the importance of adopting robust IT and knowledge management practices, alongside improving IT infrastructure, as key strategies for boosting a company’s competitive edge. Consequently, the laboratory should prioritize investments in knowledge management systems and IT infrastructure to strengthen its position in the market.
Keywords: Technological creativity; Knowledge Management; Competitive Advantage